Spinal cord lesions and brain grey matter atrophy independently predict clinical worsening in definite multiple sclerosis: a 5-year, multicentre study. Issue 1 (28th September 2022) - Rocca, Maria A; Valsasina, Paola; Meani, Alessandro; Gobbi, Claudio; Zecca, Chiara; Barkhof, Frederik; Schoonheim, Menno M; Strijbis, Eva M; Vrenken, Hugo; Gallo, Antonio; Bisecco, Alvino; Ciccarelli, Olga; et al.
Abstract : Objectives: To evaluate the combined contribution of brain and cervical cord damage in predicting 5-year clinical worsening in a multicentre cohort of definite multiple sclerosis (MS) patients. Methods: Baseline 3.0T brain and cervical cord T2-weighted and three-dimensional T1-weighted MRI was acquired in 367 patients with MS (326 relapse-onset and 41 progressive-onset) and 179 healthy controls. Expanded Disability Status Scale (EDSS) score was obtained at baseline and after a median follow-up of 5.1 years (IQR=4.8–5.2). At follow-up, patients were classified as clinically stable/worsened according to EDSS changes. Generalised linear mixed models identified predictors of clinical worsening, evolution to secondary progressive (SP) MS and reaching EDSS=3.0, 4.0 and 6.0 milestones at 5 years. Results: At follow-up, 120/367 (33%) patients with MS worsened clinically; 36/256 (14%) patients with relapsing–remitting evolved to SPMS. Baseline predictors of EDSS worsening were progressive-onset versus relapse-onset MS (standardised beta (β)=0.97), higher EDSS (β=0.41), higher cord lesion number (β=0.41), lower normalised cortical volume (β=−0.15) and lower cord area (β=−0.28) (C-index=0.81). Older age (β=0.86), higher EDSS (β=1.40) and cord lesion number (β=0.87) independently predicted SPMS conversion (C-index=0.91). Predictors of reaching EDSS=3.0 after 5 years were higher baseline EDSS (β=1.49), cord lesion number (β=1.02) and lower normalised cortical volume (β=−0.56) (C-index=0.88). Baseline age (β=0.30), higher EDSS (β=2.03), higher cord lesion number (β=0.66) and lower cord area (β=−0.41) predicted EDSS=4.0 (C-index=0.92). Finally, higher baseline EDSS (β=1.87) and cord lesion number (β=0.54) predicted EDSS=6.0 (C-index=0.91). Conclusions: Spinal cord damage and, to a lesser extent, cortical volume loss helped predicting worse 5-year clinical outcomes in MS.